EFFECT OF GROUND GRANULATED BLAST SLAG (GGBS) TO THE BONDING STRENGTH OF GEOPOLYMER MORTAR AS REPAIRING MATERIAL - Rafiza, A.R.; Zarina, Y.; Mustafa Al Bakri, A.M.; Subaer, S.; Khairunnisa, M.; Warid Wazien, A.Z.; Siang Teng, T. (Journal of Advanced Manufacturing Technology (JAMT), 2020)
The bonding strength of geopolymer mortar is very important for binding the old concrete with the latest concrete when act as repair material. The present study is aim to determine the best ratio between GGBS and fly ash in order to find the optimum bond strength under ambient temperature. There are five different ratios of GGBS to fly ash that had been tested in this research which are GGBS: FA= 10:90, 20:80, 30:70, 40:60, and 50:50. The different mixture of GGBS and fly ash is added with the alkaline solution (12M of sodium hydroxide and sodium silicate) and sand which have been mixed then rapped cured under ambient temperature. Once the mixing is done completely, pour the mixture into the metal mold and attach with the OPC concrete substrate. The bonding strength of this research were tested by using slant shear test in 7 days, 28 days and 60 days of curing. From the result tested, GGBS: FA= 30:70 could concluded as the best ratio for presenting the optimum bonding strength in this research since the bond strength for GGBS: FA=30:70 had obtain optimum strength under long curing time (9 MPa in 28 days cured and 10.6 MPa in 60 days cured). The maximum compressive strength of 46.4 MPa was observed at geopolymer mortar with GGBS: FA = 30:70. There are many factors affecting the bond strength of geopolymer which are slow setting time of fly ash and GGBS, curing temperature, size of GGBS and also the mixture proportion. The present study had concluded that GGBS: FA= 30:70 in geopolymer mortar are the best for presenting the bond strength.